2011
DOI: 10.1074/jbc.m110.211193
|View full text |Cite
|
Sign up to set email alerts
|

Defining Structural and Functional Dimensions of the Extracellular Thyrotropin Receptor Region

Abstract: The extracellular region of the thyrotropin receptor (TSHR) can be subdivided into the leucine-rich repeat domain (LRRD) and the hinge region. Both the LRRD and the hinge region interact with thyrotropin (TSH) or autoantibodies. Structural data for the TSHR LRRD were previously determined by crystallization (amino acids Glu 30 -Thr 257 , 10 repeats), but the structure of the hinge region is still undefined. Of note, the amino acid sequence (Trp 258 -Tyr 279 ) following the crystallized LRRD comprises a pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 63 publications
3
26
0
Order By: Relevance
“…However, the structure of the enigmatic ECD HR component, critical for receptor function, remained elusive. Three years ago, another major attempt to generate conformationally intact TSHR ECD and (presumably as a "back up") the isolated HR protein in yeast cells was unsuccessful (7). At the same time, our laboratory had begun a new effort (approximately our fourth) to generate these TSHR proteins in insect cells with a strategy based on the hypothesis that the redundant TSHR C-peptide portion of the HR was hindering correct folding of the proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the structure of the enigmatic ECD HR component, critical for receptor function, remained elusive. Three years ago, another major attempt to generate conformationally intact TSHR ECD and (presumably as a "back up") the isolated HR protein in yeast cells was unsuccessful (7). At the same time, our laboratory had begun a new effort (approximately our fourth) to generate these TSHR proteins in insect cells with a strategy based on the hypothesis that the redundant TSHR C-peptide portion of the HR was hindering correct folding of the proteins.…”
Section: Discussionmentioning
confidence: 99%
“…6). A more recent attempt using a yeast expression system also failed (7). Attaching a glycosylphosphatidyl inositol anchor to the TSHR ECD in lieu of the transmembrane domain does lead to efficient expression of conformationally intact protein on the surface of mammalian cells (8 -10).…”
mentioning
confidence: 96%
“…More specifically, the role for the serine in the 304 position has been explored and its substitution for alanine (p.S304A mutant) had 32% reduction in the expression and a slight but significant impairment (15%) in binding both bovine TSH (bTSH) and TR1401 (a human TSH analog) (10). Nevertheless, another study confirmed that p.S304A had decreased cell surface expression and transfection efficiency by FACS analysis, but the basal and stimulated cAMP accumulation were normal compared with WT receptor (36). Actually, the cysteine box 2/3 linker region and C-terminal portion of HinR harbor other previously described, naturally occurring inactivating mutations (p.R310C, p24X, p.C390W, p.D403N, and p.D410N), and site-directed mutagenesis studies have demonstrated that even the replacement of a single amino acid residue (e.g., p24X, p.C390W, and p.D403N) can severely impair the expression of a functional receptor protein (26,(37)(38)(39)(40)(41)(42)(43) (Table 2).…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, it was likely that the change of a polar hydrophilic S304 into a positive charged arginine residue disrupted the HinR structure, leading to a reduction in the receptor binding capacity. The p.S304R variant is located in a glycosilation HinR position within the onset of the of the cysteine box 2/3 linker region, which is known to be responsible to connect the N-and C-terminally located cysteine boxes [cysteine box 2 (C-b2) and Cysteine box 3 (C-b3)] (36). The value of the C-b2/3 linker in the maintenance of the signaling competence of the receptor has been revealed by several studies (5,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation